2005
DOI: 10.1007/s10488-005-4232-4
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Depression in Primary Care: Defragmentation in the Oregon Medicaid Market

Abstract: The Oregon Medicaid program legislatively separates the administration of physical health and mental health services, even though behavioral and physical health conditions significantly impact each other. To overcome this barrier and enhance integrated care, CareOregon, a large Medicaid only health plan partnered with two of its largest provider groups to pilot two different models of integration. In one, an "ownership" model, behavioral health specialists were employed by Federally Qualified Health Center pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…34 In fiscal year 2000-2001 alone, California county mental health programs served more than 197,000 adults with a serious mental illness 35 in a system that is carved-out from physical health care. Consistent with experiences in other states, 36 as California's Medicaid managed care (for both physical and mental health care) was implemented in the 1990s, Memorandums of Understanding were signed between the physical and mental health plans, which clarified who pays for what (such as medications) but did not organize meaningful service integration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 In fiscal year 2000-2001 alone, California county mental health programs served more than 197,000 adults with a serious mental illness 35 in a system that is carved-out from physical health care. Consistent with experiences in other states, 36 as California's Medicaid managed care (for both physical and mental health care) was implemented in the 1990s, Memorandums of Understanding were signed between the physical and mental health plans, which clarified who pays for what (such as medications) but did not organize meaningful service integration.…”
Section: Discussionmentioning
confidence: 99%
“…40 In Oregon, a Medicaid-only plan experimented with two different models of implementing the Robert Wood Johnson Foundation's "Depression in Primary care" initiative. 36 Unfortunately, there are not published data showing improvement in diabetes care.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, published studies frequently noted a conscious goal of not disrupting the existing practice. 46,47,[114][115][116][117][118][119][120][121][122][123][124][125][126] A second category of workforce innovation to address specific clinical conditions (also with 16-20 examples) was to retrain the existing staff to take on new roles. 46,47,[114][115][116][117][118][119][120][121][122][123][124][125][126] A second category of workforce innovation to address specific clinical conditions (also with 16-20 examples) was to retrain the existing staff to take on new roles.…”
Section: Matrix 2 Column 1: Transformative Workforce Innovations Focmentioning
confidence: 99%
“…Most of these programs targeted primary care clinicians, for example the eight demonstration programs funded under the Robert Wood Johnson Foundation program Depression in Primary Care: Linking Clinical and System Strategies (Barry & Frank, 2006; Frank, Huskamp, & Pincus, 2003; Pincus, Pechura, Keyser, Bachman, & Houtsinger, 2006). These programs used a variety of approaches to change the economic and organizational environment to improve care for depression, including developing new payment and billing mechanisms as well as restructuring delivery systems to better target care (Feldman, Ong, Lee, & Perez-Stable, 2006; Grazier & Klinkman, 2006; Labby, Spofford, Robison, & Ralston, 2006; Thomas, Waxmonsky, McGinnis, & Barry, 2006). A recent study identified 24 programs that use pay-for-performance approaches in behavioral health (Bremer, Scholle, Keyser, Houtsinger, & Pincus, 2008).…”
Section: Introductionmentioning
confidence: 99%